Performance of Tb Glass Used to Fabricate Special Optical Fiber as a Discrete Current Sensor - Rosolem, Joao B.; Floridia, Claudio; Bassan, Fábio R.; Nogueira, João R.; Chillcce, Enver F.; Ghezzi, Eduardo O. [UNESP]; Lodi, Thiago A. [UNESP]; Franca, Adriana M. [UNESP]; Franco, Douglas F. [UNESP]; Nalin, Marcelo [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
The performance of Tb glass used to fabricate special optical fiber is evaluated as a discrete magnetic sensor and compared with rare-earth iron garnet (RIG) based discrete sensor and silica based optical fiber sensors. The proposed material has a Verdet constant 28.8 times higher than silica. Employing a sample of Tb-glass of 5 mm length a measured sensitivity 15.6 times lower than the RIG-based sensor was achieved, proving that the proposed material can be used both as a discrete bulk element as well as an optical fiber sensing element presenting a trade-off between the silica fibers and RIG elements which cannot be pulled to form an optical fiber.
Keywords: current sensor; magnetic sensor; optical fiber sensor; Tb-glass